The Role of Accountable Village Fund Management in Supporting Village SDGs in Penusupan Village, Central Java - Diryo Suparto; Kushandajani; Ida Hayu Dwimawanti; Tri Yuningsih (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study analyzes the accountability of village fund management and its relevance to the achievement of the sustainable development goals. The village fund, mandated by Law Number 6 of 2014, has become a key instrument for supporting rural development, yet accountability issues related to planning, implementation, and reporting remain common. The study aims to assess how accountability mechanisms function at the village level and how they contribute to sustainable development outcomes. Using a qualitative descriptive approach with a case study design, data were collected through interviews with village officials, the village consultative body, and community members, as well as through analysis of the village budget and fund realization reports. The results show that the village demonstrates relatively good accountability, evidenced by transparent village meetings, public access to financial information, and the use of digital applications for fund management. However, limitations persist, including low digital literacy, limited community oversight, and potential overlap with regional programs. The study suggests strengthening institutional capacity, optimizing digital tools, and increasing community involvement to support more accountable and sustainable village governance.